Influence of microbial adherence on corrosion of UNS 1008 carbon steel and hybrid nano-structured coatings - Diaz De Rienzo, Mayri Alejandra (2018)
Purpose – Microbes that are able to grow on different surfaces can cause the deterioration of the underlying layers because of their metabolic activity. The purpose of this study is report the ability of fungi-bacteria consortium (FBC) in anaerobic media, and marine strain bacteria, to attach onto UNS 1008 carbon steel and zinc epoxy coats. Design/methodology/approach – Impedance analysis, scanning electronic microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) were used to evaluate the adherence, biofilm formation and corrosion effect of FBC and marine bacteria onto UNS1008 carbon steel in anaerobic and aired conditions, respectively. In a similar way, the anticorrosive performance of hybrid coats on UNS 1008 carbon steel against marine bacteria. Findings – In aerobic conditions, the outer layer shows a micro-crack appearance and several semi-sphere products that could be because of spore formation. In anaerobic conditions, evidence of iron sulfide surrounded by a mixture of sulfur containing extracellular polymer substance was observed by SEM images and EDS analysis. The presence of hybrid coats (zinc epoxy with carbon nanotubes CNT content) affected the level of microbial adherence and the concentration of corrosion products (Fe2O3, Fe(OH)2 and FeS); the cell attachment was lower when the steel surface was coated with Zn/CNTs. Originality/value This study opens a window for further evaluations of CNTs associated with metals as active materials to assess the corrosion on extreme corrosive environments, like in oil and gas industries the microorganisms play an important role either to increase or reduce the corrosion processes.